MEMAKNAI PROSES HIJRAH RASULULLAH MUHAMMAD SAW DARI MEKKAH KE MADINAH - Muhith Muhammad Ishaq (STAI DI AL-HIKMAH, 2024)
This study aims to interpret how migration is beneficial for a Muslim's life. Because migration is basically not only interpreted as moving from one city to another. This research method is qualitative by collecting primary and secondary data that are only sourced from libraries, namely the Qur'an, tafsir books, hadiths, journals, and research published online. The conclusion of the study is that migration from Mecca to Medina is an important event in Islamic history that involves emotions and drains feelings because it has to leave an environment that has been a part of life for decades, and has fostered deep love that provides many beautiful memories, towards a new environment that gives hope for the future. This passion of love is what underlies the beautiful attitude of the Prophet Muhammad SAW in treating both of them, even though an event has occurred that allows someone to be disappointed, because a pious person when he loves will try to honor it and when disappointed will not oppress it.